Regulatory Perspectives On Islamic Banking And Sharia Economic Development: Evidence From Pari City, Serdang Bedagai, North Sumatra - M Erwin Radityo; Beby Sendy; Tria Wahyu Artita (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study explores the regulatory dimensions of Islamic banking law and its contribution to the development of Sharia-based economic programs in North Sumatra, Indonesia, focusing on Pari City, Serdang Bedagai Regency. The research aims to examine how the implementation of Islamic banking regulations supports the expansion of the Sharia economy at the regional level. A qualitative descriptive method was employed, combining legal and economic approaches through field observations, document analysis, and semi-structured interviews with key stakeholders, including Islamic banking practitioners, local government officials, and small and medium enterprises (SMEs) engaged in Sharia-based business models. The results indicate that Islamic banking law provides a strong legal foundation for the development of ethical financial practices and community-based economic empowerment. However, its effectiveness is constrained by limited regulatory enforcement, low public literacy in Sharia finance, and inadequate coordination between financial institutions and regional authorities. The study finds that the integration of regulatory reform, education, and community engagement can significantly enhance the inclusivity and sustainability of the Sharia economic ecosystem. This research contributes to the growing body of knowledge on the intersection between law, finance, and regional economic development in Muslim-majority societies. It emphasizes the importance of adaptive legal frameworks and institutional support to strengthen Islamic banking’s role in achieving equitable and sustainable growth in Indonesia’s regional economies.